The Use of Group Discussions to Improve the Achievement in Speaking Skill - Manafe, Erna Maya (e-Journal of Linguistics, 2020)
This is a pre- experimental research which used one group pre- test and post-test design. The objective of this research was to know the effectiveness of group discussion in improving the students’ English language learning using group discussion. The populations of this research were the ninth grade students of SMPN 13 Maulafa Kupang numbering 233 students. The samples of this research were 35 students. The variables of the research were the students’ achievement, as depend on variable, and the use of group discussion as the independent variable. The method of collecting data used in this research was pre-test that was given before treatment and post-test that  was given after treatment to analyzed the data, the writer used t-test formula. the result of the research showed that the score of the t-test in the first session was 11.15, while in the second session was 14. The score of t-table for level of significant for df 34 in level 0.05 is 2.30 and in level 0.01 is 2.73. After comparing the score of t-test and t-table, it means that group discussion can significantly improve the students’ achievement in English speaking ability. Besides, it also can make the class active, alive, and motivate student to work together to develop and share ideas more freely. The problems that make the students were difficult in speaking was the lack of vocabulary mastery.